Pengembangan Bahan Ajar Digital Pada Mata Pelajaran Projek Kreatif - Cici Yulihendri; Susi Evanita (Postgraduate, University of Mataram, 2023)
This research aims to produce valid, practical and effective digital teaching materials for the Creative Projects and Entrepreneurship subjects in Class XI of SMK Negeri 2 Padang. Also, to see students' interest in learning using Digital Teaching Materials. The design of this digital teaching material uses the heyzine flipbook application. This research uses the Research and Development (R&D) method using the ADDIE development model with the stages of Analysis, Design, Development, Implementation and Evaluation. The research results show that the development of digital teaching materials has met the criteria of being valid, practical and effective for use in learning. The validation results from language experts were 97%, material validation was 94.91% and media experts were 87.20% in the very valid category. The assessment of teacher practicality was 89.17% and student practicality was 82.06%, which fell into the very practical category. With an effectiveness of 75.83%, it falls into the effective category and can improve student learning outcomes. Also, students' interest in learning was 87.39% in the very good category. So, it can be concluded that digital teaching materials are suitable for use in learning Creative Projects and Entrepreneurship.